Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/mp/ssu102
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Arabidopsis Calmodulin-Like Protein CML37 Deregulates the Jasmonate Pathway and Enhances Susceptibility to Herbivory

Abstract: Throughout their life, plants are challenged by various abiotic and biotic stress factors. Among those are attacks from herbivorous insects. The molecular mechanisms underlying the detection of herbivores and the subsequent signal transduction are not well understood. As a second messenger, fluxes in intracellular Ca(2+) levels play a key role in mediating stress response pathways. Ca(2+) signals are decoded by Ca(2+) sensor proteins such as calmodulin-like proteins (CMLs). Here, we demonstrate that recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
122
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 65 publications
(87 reference statements)
3
122
0
1
Order By: Relevance
“…12 Recently, several CMLs were identified that are regulated by herbivory or herbivore-related signals present in insect-derived oral secretions. [13][14][15] For 2 particular calmodulin-like proteins, CML37 and CML42, it was demonstrated that they have antagonistic effects. CML42 represents a negative regulator of insect herbivory-induced defense, while CML37 is quite the opposite, a positive regulator of insect herbivoryinduced defense.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Recently, several CMLs were identified that are regulated by herbivory or herbivore-related signals present in insect-derived oral secretions. [13][14][15] For 2 particular calmodulin-like proteins, CML37 and CML42, it was demonstrated that they have antagonistic effects. CML42 represents a negative regulator of insect herbivory-induced defense, while CML37 is quite the opposite, a positive regulator of insect herbivoryinduced defense.…”
mentioning
confidence: 99%
“…CML42 represents a negative regulator of insect herbivory-induced defense, while CML37 is quite the opposite, a positive regulator of insect herbivoryinduced defense. 13,15 CML37 was shown to connect Ca 2C and jasmonate signaling by affecting the synthesis of jasmonic acidisoleucine conjugate. 15 All those examples demonstrate that almost all CML genes studied so far are involved in more than one stress-responsive pathway, including biotic and abiotic stress, as well as developmental stimuli.…”
mentioning
confidence: 99%
“…17 Recently CML37, a Ca 2C sensor involved in the regulation of herbivore-induced plant defenses mediated by jasmonates was also identified as a positive regulator of ABA in drought stress. 18 The cml37-1 mutant displays a lower expression of JA related genes in response to wounding and, interestingly, this mutant also has a reduced ABA accumulation in response to drought stress, 19 moreover, another member of this Ca 2C sensor family, CML42 has antagonistic effects and Arabidopsis mutant defective in this protein is able to accumulate ABA in response to drought.…”
mentioning
confidence: 99%
“…While CML42 acts as a negative regulator of plant defense against herbivorous insects, CML37 acts as a positive regulator. [15][16][17] In response to drought stress, CML37 and CML42 also act as positive and negative regulators respectively. 15,16 Collectively, all these data highlight the complexity of calcium signaling in plant and support the idea that CMLs could be at the crossroads of plant biotic and abiotic stresses signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In response to drought stress, CML37 and CML42 also act as positive and negative regulators respectively. 15,16 Collectively, all these data highlight the complexity of calcium signaling in plant and support the idea that CMLs could be at the crossroads of plant biotic and abiotic stresses signaling pathways. CMLs can exhibit a dual function as either positive and/or negative regulators in plant stresses and thus, might be involved in the fine tuning of plant physiological responses to pathogens under fluctuating parameters of the environment (i.e., temperature, water availability).…”
Section: Introductionmentioning
confidence: 99%